2019
DOI: 10.1101/642405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biological Aging in Childhood and Adolescence Following Experiences of Threat and Deprivation: A Systematic Review and Meta-Analysis

Abstract: Life history theory argues that exposure to early-life adversity (ELA) accelerates development, although existing evidence for this varies. We present a meta-analysis and systematic review testing the hypothesis that ELA involving threat (e.g., violence exposure) will be associated with accelerated biological aging across multiple metrics, whereas exposure to deprivation (e.g., neglect, institutional rearing) and low-socioeconomic status (SES) will not. We meta-analyze 46 studies (n=64,925) examining associati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
80
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(89 citation statements)
references
References 219 publications
(305 reference statements)
8
80
0
1
Order By: Relevance
“…These clocks showed the expected associations with children's chronological age (r = 0.66-0.81 in an age range of 8-18 years). However, the difference between participants' epigenetic ages and their chronological ages, i.e., epigenetic age acceleration, did not differ between children experiencing different levels of socioeconomic risk, consistent with results from a recent meta-analysis (23). Measures of epigenetic age acceleration also appear to be less sensitive to racial/ethnic group differences in childhood and adolescence (22).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These clocks showed the expected associations with children's chronological age (r = 0.66-0.81 in an age range of 8-18 years). However, the difference between participants' epigenetic ages and their chronological ages, i.e., epigenetic age acceleration, did not differ between children experiencing different levels of socioeconomic risk, consistent with results from a recent meta-analysis (23). Measures of epigenetic age acceleration also appear to be less sensitive to racial/ethnic group differences in childhood and adolescence (22).…”
Section: Discussionsupporting
confidence: 84%
“…Not all types of adversity show evidence of association with clock measurements. In particular, low childhood socioeconomic status, which is consistently associated with shorter healthy lifespan, is not consistently associated with epigenetic clock measures of aging (23).…”
mentioning
confidence: 92%
“…In a recent meta-analysis-including 43 studies of pubertal timing with 114,450 participants and 11 studies of cellular aging with 1560 participants-we found that the association between ELA and accelerated biological development was specific to adversities involving exposure to trauma. Specifically, children exposed to trauma exhibited accelerated biological aging in measures of pubertal development and cellular aging, but children exposed to deprivation (e.g., neglect) and low socioeconomic status did not exhibit this pattern of accelerated aging [110]. These results support dimensional models of adversity arguing that different forms of earlylife adversity have unique influences on cognitive, emotional, and neurobiological development [32][33][34].…”
Section: Accelerated Biological Agingmentioning
confidence: 84%
“…The single previous longitudinal investigation operationalized ELS as a composite of parent-reported depression, perceived stress, and family expressed anger (Ruttle et al, 2015). There is evidence that different forms of ELS have differential effects on psychobiological development (King et al, 2019;Lambert et al, 2017;Sheridan et al, 2017) and, in particular, that exposure to environmental threat (as opposed to deprivation) accelerates biological development (Colich et al, 2019;Del Giudice et al, 2011). Therefore, measures that combine exposure to different forms of ELS make it difficult to identify directional hypotheses or to determine what form of stress confers risk.…”
Section: The Current Studymentioning
confidence: 99%
“…Given evidence that exposure to environmental threat (as opposed to deprivation) accelerates biological development (Colich et al, 2019;Del Giudice et al, 2011), we hypothesized that greater severity of threat-related ELS is associated with stronger positive coupling between change in cortisol and change in DHEA, and with weaker positive coupling between change in cortisol and change in testosterone across development.…”
Section: The Current Studymentioning
confidence: 99%